Sensitivity of Acoustic Emission Triggering to Small Pore Pressure Cycling Perturbations During Brittle Creep. Issue 13 (15th July 2019) - Chanard, K.; Nicolas, A.; Hatano, T.; Petrelis, F.; Latour, S.; Vinciguerra, S.; Schubnel, A.
Abstract: Fluid‐induced stress perturbations in the crust at seismogenic depths caused by sources such as tidal or seasonal loading may trigger earthquakes. We investigate the role of small periodic pore pressure ( P p ) perturbation in rupture nucleation by performing laboratory triaxial creep experiments on Fontainebleau sandstone, saturated in water, under sinusoidal P p variations. Results show that recorded acoustic emissions (AEs) correlate with P p as the rock approaches failure. More interestingly, AEs occur significantly more when P p is decreasing, that is, when strain rate is maximum with a progressive increase of P p ‐AEs correlation in time as the rock approaches failure. This suggests that the correlation of small stress perturbations and AEs not only depends on P p amplitude but also on the criticality of the rock. Observations at the laboratory scale support field observations where tidal loading may have modulated seismic rates during the nucleation phase of the 2004 Sumatra‐Andaman and 2011 Tohoku‐Oki earthquakes. Key Points: We investigate the role of periodic pore fluid pressure on AEs triggering during creep deformation experiments AEs correlation with pore pressure oscillations increases as the rock approaches failure AEs occur significantly more when pore pressure decreases, that is, when deformation is maximum